A new chiral rare‐earth organic framework constructed by tartaric acid: synthesis, structural, thermal investigations and optical properties. Issue 5 (26th April 2022) - Belhouas, Ratiba; Trifa, Chahrazed; Bouacida, Sofiane; Benmerad, Belkacem; Souici, Abdel Hafid; Boudaren, Chaouki; Merazig, Hocine
Abstract : A new Ce III coordination polymer based on the tartrate ligand has been prepared and structurally characterized. It exhibits good thermal stability and photoluminescence properties. The IR spectra, UV spectra and PXRD patterns were investigated and a Hirshfeld surface analysis was carried out. Abstract : Hydrothermal reactions of rare‐earth cerium with l ‐tartaric acid afford a new coordination polymer, namely, poly[[triaqua(μ4 ‐l ‐tartrato)cerium(III)] chloride], {[Ce(C4 H4 O6 )(H2 O)3 ]Cl} n, (1). The structure was determined by single‐crystal X‐ray diffraction analysis and further characterized by IR and UV–Vis spectroscopy, powder X‐ray diffraction and thermogravimetric analysis. Single‐crystal X‐ray diffraction analysis revealed that the compound is a new two‐dimensional (2D) double‐layered structure with one‐dimensional left‐handed helical chains. The different intermolecular interactions were confirmed using Hirshfeld surface analysis and molecular fingerprint plots. Molecular 2D fingerprint plots quantify the different interactions and highlight that H…H (24.8%), H…O/O…H (26.3%), Cl…H/H…Cl (19.6%), O…O (13.8%) and Ce…O/O…Ce (13.6%) interactions account for 99.8% of all contacts. Additionally, the photoluminescence properties of the compound were investigated in the solid state.